2020
DOI: 10.1161/atvbaha.119.313800
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-126-3p Inhibits Angiogenic Function of Human Lung Microvascular Endothelial Cells via LAT1 (L-Type Amino Acid Transporter 1)-Mediated mTOR (Mammalian Target of Rapamycin) Signaling

Abstract: Objective: MicroRNA-126-3p (miR-126) is required for angiogenesis during organismal development or the repair of injured arterial vasculature. The role of miR-126 in lung microvascular endothelial cells, which are essential for gas exchange and for lung injury repair and regeneration, remains poorly understood. Considering the significant heterogeneity of endothelial cells from different vascular beds, we aimed to determine the role of miR-126 in regulating lung microvascular endothelial cell funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…As shown in (Figure 4a,4b), Bcl-2 levels decreased markedly in cardiac myocytes subjected to hypoxia/ acidosis or aerobic acidosis, and the effects were blocked by KD of miR-126 in parallel with reduced apoptosis. The results suggest negative regulation of anti-apoptotic Bcl-2 by miR-126 in this model that is consistent with some previous results [41,43,44]. We quantified the expression levels of p38-MAPK and JNK in hypoxic/acidotic and aerobic-acidotic cardiac myocytes in the presence and absence of miR-126 KD.…”
Section: Roles For Bcl2 and Mapk/jnk In Mir-126-mediated Inflammation And Apoptosissupporting
confidence: 92%
“…As shown in (Figure 4a,4b), Bcl-2 levels decreased markedly in cardiac myocytes subjected to hypoxia/ acidosis or aerobic acidosis, and the effects were blocked by KD of miR-126 in parallel with reduced apoptosis. The results suggest negative regulation of anti-apoptotic Bcl-2 by miR-126 in this model that is consistent with some previous results [41,43,44]. We quantified the expression levels of p38-MAPK and JNK in hypoxic/acidotic and aerobic-acidotic cardiac myocytes in the presence and absence of miR-126 KD.…”
Section: Roles For Bcl2 and Mapk/jnk In Mir-126-mediated Inflammation And Apoptosissupporting
confidence: 92%
“…Endothelial cell apoptosis plays an important role in vascular degeneration and vascular remodeling during angiogenesis, which is closely related to the process of the aortic arch, lens vascular membrane development, and wound healing, and can also disrupt the formation of the vascular network and inhibit tumor progression ( Affara et al, 2007 ; Ehling et al, 2020 ; Sun et al, 2020 ). Studies have shown that promoting endothelial cell apoptosis can inhibit angiogenesis, which is beneficial in the treatment of diseases related to microvascular proliferation ( Cao et al, 2020 ). Activated caspase 9 and caspase 3 are key downstream proteins in the apoptotic protein cascade and are the main indicators of apoptosis ( Kang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…153 Furthermore, studies have confirmed that LAT1 is the target of microRNA-126. 158,159 In summary, we can conclude that LAT1 plays an important role in the amino acid metabolism of TC. Various factors in TC caused alterations in LAT1 expression, and LAT1 transported more leucine through these changes to meet the metabolic needs of TC, thus promoting the development of TC.…”
mentioning
confidence: 69%